2019
DOI: 10.1002/joc.6428
|View full text |Cite
|
Sign up to set email alerts
|

Time‐lagged correlations associated with interannual variations of pre‐monsoon and post‐monsoon precipitation in Myanmar and the Indochina Peninsula

Abstract: The time‐lagged correlations of monthly precipitation in Myanmar and the Indochina Peninsula (ICP) with several climate indices were investigated by using Global Precipitation Climatology Centre dataset after checking its quality with rain‐gauge data. The results showed significant time‐lagged correlations of several climate indices related to El Niño‐Southern Oscillation and El Niño Modoki with precipitation anomalies in Southern Myanmar during pre‐monsoon (April) and post‐monsoon (October) months. Composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…According to the Asia-Pacific monsoon division by Wang (2002), Myanmar Coast is located in the Indian monsoon subsystem. This region experiences three different weather seasons in the year: the winter or dry and cool season from November to February, the summer or hot season from March to April, and the rainy or southwest monsoon season from May to October (Lwin 2000;Aung et al 2017;Chhin et al 2020). Climatologically, precipitation in the monsoon season accounts for 95% of total precipitation while the remaining 5% occurs in the other half year.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Asia-Pacific monsoon division by Wang (2002), Myanmar Coast is located in the Indian monsoon subsystem. This region experiences three different weather seasons in the year: the winter or dry and cool season from November to February, the summer or hot season from March to April, and the rainy or southwest monsoon season from May to October (Lwin 2000;Aung et al 2017;Chhin et al 2020). Climatologically, precipitation in the monsoon season accounts for 95% of total precipitation while the remaining 5% occurs in the other half year.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, water vapor is transported by the low-level westerly over the Indian Ocean and the southeasterly associated with the subtropical ridge over the North Pacific. The moisture transport for precipitation over the Indochina Peninsula exhibits an apparent intraseasonal variability (Chhin et al, 2019). Prior to the onset of the summer monsoon, water vapor for precipitation is mainly contributed by the enhancement of moisture transport from the Bay of Bengal.…”
Section: Introductionmentioning
confidence: 99%
“…The climatological seasonal evolution of monsoon rainfall in ICP is divided into three steps: pre‐monsoon, summer monsoon (from onset to withdrawal dates), and post‐monsoon seasons (Matsumoto, 1997; Chhin et al ., 2019). Matsumoto (1997) called the early start of rainy season over the inland region of ICP from late April to early May as “pre‐monsoon rain”.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies focus on the summer monsoon rainfall and its onset in ICP (Kripalani et al ., 1995; Chen and Yoon, 2000; Wu and Wang, 2000; Zhang et al ., 2002; Mao and Wu, 2007; Takahashi and Yasunari, 2008; Feng et al ., 2013; Xiang and Wang, 2013; Takahashi et al ., 2014; Nguyen‐Le et al ., 2015; Liu et al ., 2016; Luo et al ., 2016; Ge et al ., 2017; Li et al ., 2018), there are only a few studies which reported the pre‐monsoon rainfall in the region (Kiguchi and Matsumoto, 2005; Kiguchi et al ., 2016; Chhin et al ., 2019). Passage of the upper atmospheric trough that migrates eastward in the mid‐latitude westerly zone along the southern periphery of the Tibetan Plateau and the associated moisture convergence in the lower troposphere produce intermittent rainfall events in the pre‐monsoon period (Kiguchi and Matsumoto, 2005; Kiguchi et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation